IGG4-RELATED DISEASE: CONDITION OF THE PROBLEM - V. V. Vasilenko; D. L. Vinogradov; A. S. Burlakova (Архивъ внутренней медицины, 2017)
The physiological role of IgG4 is poorly understood yet. It is known, that they, like other antibodies, are involved in the inactivation and removal of organism agent, which are identified as foreign antigens by immune system. IgG4 also release effector mechanisms: contact  with the specialized immune  cells, which perform  phagocytosis  foreign antigens  or destruction  of the  infected  cells by antibody-dependet cytotoxicity,  after  this interaction. Opinions about the ability to activate complement system are divided. The elevation concentration of that subclass immunoglobulins can be an indicator not only of development of infectious and allergic conditions, but also the presence of the IgG4-related disease in a patient´s organism. IgG4-rd is a recently selected group of pathological conditions and it is becoming relevant to study. It is because they include the conditions, which have been thought  to be separate  nosology previously. In recent years IgG4 –RD has been diagnosed more often, because it has been increasingly being recognized in the medical community. This review includes the latest information from the latest foreign publication.